we all know the quadratic formula: (-b+-?b2-4ac)/2a
and this we know will give us two answers for x
so what we know are: A,B,C ANSWER 1 AND ANSWER 2 (which we'll call A1 and A2)
ok now so we'll start with an equasion in radical form:
(2x+6)(3x+9)=0 when you do the foil method this turns into:
and we know x=-3 and x=-3 (that worked out nicely)
ok so for this equasion
A=6........A1=-3 B=36.......A2=-3 C=54
now i want to be able to change this into radical form just knowing that information. so here's what i've come up with (remember the equasion in radical form is: (2x+6)(3x+9) so i've given variable names to those numbers in the radical form of the equasion in order W,X,Y,Z
so in this case,
W=2 X=6 Y=3 Z=9
see what i'm saying?
ok so i've defined each variable you might have to look at this for a while to see what i'm saying remember we only know a,b,c,a1,and a2 we don't know W,X,Y,or Z.
if you think about it you'll see what i'm talking about so what i want is to define at least one variable using only the information I know (A,B,C,AN1,AN2) so i start with (using what i know from the above info): NOTE: A MEANS A/Z THERE IS NO UNDERLINE SORRY ..........Z